Investigation of enhanced electrocoagulation-membrane process for water reclamation from palm oil mill effluents - Tahreen, Amina; Jami, Mohammed Saedi; Ali, Fathilah; Nik Abdul Ghani, Nik Rashida; Nedjai, Radhia (IIUM Press, 2024)
The process of electrocoagulation (EC) enhanced with adsorbent addition, as a pre-treatment for ultrafiltration membrane, is widely unexplored in oil palm-based wastewater treatment. Utilizing predetermined EC operational parameters and a defined activated carbon (AC) dosage for biotreated palm oil mill effluents (BPOME), membrane fouling was studied during crossflow membrane filtration at 0.5 bar transmembrane pressure and 1 kDa membrane pore size. The dominant fouling mechanism in membrane filtration without EC-AC pretreatment of BPOME, was cake formation, which was determined through Hermia’s pore blocking models. However, after EC-AC pre-treatment, the membrane fouling was mitigated. Moreover, the pre-treatment process, AC assisted EC, sustainably enhanced the final treated effluent quality in addition to enhancing fouling mitigation in the subsequent membrane filtration. The removal of Total Suspended Solids (TSS), turbidity and color were nearly 100% and Chemical Oxygen Demand (COD) was 99.7% removed with final value of 5±1 mg/L, which is within the range of reusable water standards. ***** Proses elektrokoagulasi (EC) yang ditingkatkan dengan bahan penyerap, adalah pra-rawatan bagi membran penuras ultra. Walau bagaimanapun ianya masih belum luas diterokai dalam sistem rawatan air buangan berasaskan kelapa sawit. Mengguna pakai parameter operasi EC pra-tentu dan dos karbon aktif tentu (AC) bagi bio-rawatan efluen kilang kelapa sawit yang terawat (BPOME), mendakan membran telah dikaji menggunakan teknik penurasan membran aliran silang pada tekanan transmembran 0.5 bar dan saiz liang membran 1 kDa. Mekanisme mendakan membran kotoran dominan dalam penurasan membran tanpa pra-rawatan EC-AC BPOME, adalah pembentukan kek, iaitu terhasil melalui model penyumbatan liang Hermia. Walau bagaimanapun, selepas pra-rawatan EC-AC, mendakan kotoran membran dapat dikurangkan. Tambahan, proses pra-rawatan AC-EC, secara mampan dapat menambah kualiti akhir efluen terawat selain dapat meningkatkan mitigasi kotoran mendakan dalam penurasan membran seterusnya. Penyingkiran Total Pepejal Terampai (TSS) adalah 99.7%, kekeruhan dan warna adalah hampir 100%. Keperluan Oksigen Kimia (COD) tersingkir sebanyak 99.7% dengan nilai akhir sebanyak 5±1 mg/L, iaitu dalam julat piawaian air boleh guna semula.